2014
DOI: 10.1089/scd.2014.0064
|View full text |Cite
|
Sign up to set email alerts
|

Sphere Formation Permits Oct4 Reprogramming of Ciliary Body Epithelial Cells into Induced Pluripotent Stem Cells

Abstract: Somatic cells can be reprogrammed to induced pluripotent stem (iPS) cells by defined sets of transcription factors. We previously described reprogramming of monolayer-cultured adult mouse ciliary body epithelial (CE) cells by Oct4 and Klf4, but not with Oct4 alone. In this study, we report that Oct4 alone is sufficient to reprogram CE cells to iPS cells through sphere formation. Furthermore, we demonstrate that sphere formation induces a partial reprogramming state characterized by expression of retinal progen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
(47 reference statements)
1
4
0
Order By: Relevance
“…These data suggest that the culture condition in spheroids has the effect of rejuvenating hCPCs, which acquire the potential of more cell cycles [ 56 ]. This observation is in line with what recently reported for cells from ciliary body, which, if in spheroids, could be reprogrammed in the presence of only Oct4, not requiring Klf4, which otherwise was necessary if cells were maintained as monolayers [ 57 ]. The fact that hCPCs are able to modulate positively and negatively telomerase depending on the culture conditions is noteworthy, since it indicates that the cells have not a tumoral behaviour but retain a stem cell profile.…”
Section: Discussionsupporting
confidence: 91%
“…These data suggest that the culture condition in spheroids has the effect of rejuvenating hCPCs, which acquire the potential of more cell cycles [ 56 ]. This observation is in line with what recently reported for cells from ciliary body, which, if in spheroids, could be reprogrammed in the presence of only Oct4, not requiring Klf4, which otherwise was necessary if cells were maintained as monolayers [ 57 ]. The fact that hCPCs are able to modulate positively and negatively telomerase depending on the culture conditions is noteworthy, since it indicates that the cells have not a tumoral behaviour but retain a stem cell profile.…”
Section: Discussionsupporting
confidence: 91%
“…Spheroid formation in ULAPs, as a classical method to form suspended 3D spheroids, is widely utilized for many cell types (Ni et al, 2014;Bu et al, 2020). Byun et al (2014) found that stemness transcription factor genes (NANOG and OCT4) were upregulated during suspended 3D spheroid culture in ULAPs.…”
Section: Discussionmentioning
confidence: 99%
“…Though experimental tumors have been created from ciliary body stem cells, in general, the term medulloepithelioma is reserved for embryonic neoplasms believed to arise from embryonal or fetal tissues, making ‘embryonal medulloepithelioma' redundant and ‘adult medulloepithelioma' contradictory [5,6,7]. At least 16 cases of medulloepithelioma have been reported in patients older than 20 years, with the oldest in a 79-year-old man [9,10].…”
Section: Discussionmentioning
confidence: 99%